MENINGKATKAN PROFESIONALITAS GURU - Ayu Ratna Wulandari (Perspektif Ilmu Pendidikan, 2009)
Profesionalism should be possessed by every teacher in performing their tasks professionally. Besides every teacher should improve her/his competence by his/her own efforts, the school pricincipal should develop the teachers professionalism. This reasearch aimed at describing the school principal’s role to improve the teachers profesionalism by choosing StateVocational Senior Secondary School 6 in Jakarta as a case study. This study, conducted as from March through June 2009, collected data using interview and observation techniques and analyzed the data descriptively to answer the researcg questions. This reserach concluded thet the school principal in StateVocational Senior Secondary School 6 in Jakarta did various techniques in assissting the teachers to improve their professionalism. To complete the research findings, the implications of the study and some recommendations were presented for further considerations.